Anaerobic treatment of sugar waste water using a granular bed upflow anerobic sludge blanket reactor - Anglo, P.G; Santiago, C.M.,Jr; Silverio, C.M; Montero, G. (1988)
An Upflow Anaerobic Sludge Blanket reactor (UASB) was designed, fabricated, and tested as a means of wastewater treatment in sugar milling industries. This reactor substantially reduced the COD [chemical oxygen demand] level of the effluent by 80-92% after a 40-day period of anaerobic fermentation. Biogas production significantly increased and was stabilized at approximately 16 liters daily within this period. The UASB process produced high sludge concentration resulting in an efficient biodegradation of organic matter. Furthermore, it can be operated in a relatively shorter hydraulic retention time of 1-4 days.